Active real-time control of Alfvén eigenmodes by neutral beam and electron cyclotron heating in the DIII-D tokamak. (17th September 2018) - Hu, Wenhui; Olofsson, K.E.J.; Welander, A.S.; Heidbrink, W.W.; Van Zeeland, M.A.; Austin, M.E.; Collins, C.S.; Humphreys, D.A.; Kolemen, E.; Li, Jiangang; Xiao, Bingjia
Abstract: A real-time Alfvén eigenmode (AE) controller is designed and implemented for the first time in DIII-D. The experimental test consists of two parts: (i) open-loop and feedback control using neutral beam power as an actuator and (ii) open-loop control using electron cyclotron heating (ECH) as an actuator. Part (i) demonstrates the feasibility of varying neutral beam power injected into plasma to control overall AE amplitude as well as the successful application of real-time electron cyclotron emission (ECE) as the process controller's AE amplitude sensor. The temporal evolution of AE amplitude at a specific radial location has also been controlled by selecting a subset of the radial ECE array. Part (ii) finds a complicated dependence of AE evolution on ECH power and more dedicated investigation is needed to explore the dynamical ECH-control model. Additionally, the ratio between TRANSP calculated neutron rate and measured neutron rate is found to correspond closely with AE amplitudes in discharges with feedback control, verifying that this ratio can be another sensor for the control system.